ENHANCED AN EMPLOYEED ANALYSIS OF COMPETENCIES, JOB CHARACTERISTICS, AND JOB SATISFACTION ON PERFORMANCE - Aminuddin Aminuddin (Sean Institute, 2023)
The purpose of this research is to determine and analyze the influence of competency, job characteristics and job satisfaction on employee performance at Hotel Saka Medan. This type of research is quantitative research. The sampling technique is bySamplingThe saturation used in this research were 55 employees who worked at Hotel Saka Medan. The method used in this research is multiple linear regression analysis method. Based on the t test (partial), the competency variable has a positive and significant effect on employee performance, job characteristics have a negative and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance at Hotel Saka Medan. Based on the F test (simultaneous), the variables of competency, job characteristics and job satisfaction have a positive and significant effect on employee performance at Hotel Saka Medan. Markadjusted R Square amounting to 0.912 indicates that competency, job characteristics and job satisfaction account for 91.2% of employee performance variables while the remaining 8.8% is explained by other variables or factors not included in this research.